A bibliography of the works of Christopher Duggan. Issue 4 (4th October 2017) - Oglethorpe, Stuart
Abstract : This is a full bibliography of the works of Christopher Duggan, including his D.Phil thesis, books, contributions to edited collections, articles in journals, newspapers and other periodicals, book reviews and review articles. It illustrates both the range of his own scholarship and his engagement with the fields of modern Italian history, politics, society and culture.